Hubungan antara Komunikasi Interpersonal dengan Kinerja Guru SMK Swasta di Kecamatan Bogor Utara Kota Bogor - Wisnu Diputra; Neti Karnati; Matin Matin (Universitas Negeri Jakarta, 2017)
This study aims to know there is a relationship between headmasters interpersonal communication with teachers performance at Vocational High School North Bogor District, Bogor City. This research use quantitative with two variables there in, namely: (X) interpersonal communication as independent variable and (Y) teachers performance as the dependent variable. The method used is survey method with the results of the analysis of correlational studies. The population in this study are teachers at vocational high school in North Bogor District, Bogor City, there are 580 teachers. Samples were taken by using simple random sampling technique. The technique is based on the sample size used in this study as many as 85 teachers. Data collection for the variable (X) interpersonal communication and variable (Y) teachers performance using a questionnaire. Hypothesis testing is done by using product moment correlation formula and getting the correlation coefficient (r) value = 0,58892 and based on the results of hypothesis testing by using t-test obtained t for 6,639 Ëƒ 1,671 t-tables. By this research, we get a positive relation between interpersonal communication with teachers performance at Vocational High School North Bogor District, Bogor City.